Cat ninja. 2, Time heist - Cody, Matthew; Mercado, Yehudi (Epic! originals., 2021)
"Villains are flooding into Metro City, and it doesn't take a criminal mastermind to realize they're all after the same thing--Cat ninja! Plus Leon brings home a mystery egg that hatches into an excitable owlet named Hoot, confronting our hero with his biggest challenge yet: babysitting! When Cat ninja discovers Hoot's connection to the sudden wave of baddies, he'll need his paw-some family's help to save the baby owl, the city...and the future"--Back cover.